A Novel Compact Microstrip Lowpass Filter with Sharp Transition and Improved Stopband - Pingjuan Zhang; Minquan Li (Institute of Advanced Engineering and Science, 2015)
A novel compact microstrip lowpass filter (LPF) is proposed in this paper, which consists of the complementary rectangle split ring defected microstrip structure (CRSR-DMS), open stubs, spurline and the dumbbell-shaped defected ground structure (DGS). Due to the unique response of the presented CRSR-DMS, a low passband insertion loss and a sharp transition of the proposed LPF was achieved. Meanwhile, an improved stopband was obtained by properly adjusting the working frequencies of open stubs, a third-order LPF using spurline and dumbbell-shaped DGS. The measured result of the designed LPF shows that attenuation rate reaches 159 dB/GHz and a wide stopband is obtained from 4.07 GHz to more than 15 GHz. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6760